Shakespeare across the Taiwan Strait: A Developmental Perspective - Sun, Yu; Zhang, Longhai (Multicultural Shakespeare: Translation, Appropriation and Performance, 2019)
Shakespeare studies in Mainland China and Taiwan evolved from the same origin during the two centuries after Shakespeare being introduced into China in the early nineteenth century. Although Shakespeare was first seen on the Taiwan stage in the Japanese language during the colonial period, it was after Kuomintang moved to Taiwan in 1949 that Shakespeare studies began to flourish when scholars and theatrical experts from mainland China, such as Liang Shih-Chiu, Yu Er-Chang, Wang Sheng-shan and others brought Chinese Shakespeare to Taiwan. Since the 1980s, mainland Shakespeareans began to communicate actively with their colleagues in Taiwan. With the continuous efforts of Cao Yu, Fang Ping, Meng Xianqiang, Gu Zhengkun, Yang Lingui and many other scholars in mainland China and Chu Li-Min, Yen Yuan-shu, Perng Ching-Hsi and other scholars in Taiwan, communications and conversations on Shakespeare studies across the Taiwan Strait were gradually enhanced in recent years. Meanwhile, innovations in Chinese adaptations of Shakespeare have resulted in a new performing medium, Shake-xiqu, through which theatrical practitioners on both sides explore possibilities of a union of Shakespeare and traditional Chinese theatre. This paper studies some intricate relationship in the history of Shakespeare studies in mainland China and Taiwan from a developmental perspective and suggests opportunities for positive and effective co-operations and interactions in the future.